Efektifitas Work From Anywhere Pada Era Digital - Nur Evika Kamiliyatun Ni’mah; Wahyu Eko Pujianto (Universitas 45 Surabaya, 2023)
This study aims to find out new habits from the work from anywhere phenomenon in the era digital after the Covid-19 pandemic. This research is a descriptive research using survey method and looking at previous research. As we know that the Covid-19 pandemic changed many things and also created new habits that were previously thought impossible. One of the new habits is that it is widely practiced in the business sector that companies choose to Work From Anywhere or Work From Home. Working without having to be in the work office or can be done from anywhere is a solution when we are in a situation where it is not possible to do work in the office directly. Working remotely also provides freedom for workers to carry out their duties anywhere and anytime by utilizing existing technology. The reason why employees and companies choose such a policy is because it prevents the spread of the Covid-19 virus where they work. On the other hand, the Work From Anywhere work system is supported by the growing development of digital technology and the smarter generation of today. In general, people who work WFH say that working with a system like this is better than having to work that requires coming directly to the workplace. This is also supported by digital technology that is increasingly sophisticated and used correctly so there is no reduction. performance.